Intercultural Mediation and Accessibility in Heritage - HAMAOUI, NAJWA KH; STAVROU, CHRISTOS (International Journal of Language, Translation and Intercultural Communication, 2019)
This article aims to propose a strategy taking in consideration the accessibility of each European citizen to information in all its forms especially audio-visual Media and Heritage. It is known that interlingual mediators are playing a huge part in the world of Information and Communication with the involving difficulties of common core theory and training. Moreover, technology can be the ideal tool to enhance accessibility. Thus, mobile phone applications can offer sometimes both audio and visual content to Museum visitors as well as sign language and text. This part of our work clarifies the needs and the values of an adapted methodology for training. In addition, this project gives to inter-cultural mediators the opportunity to work and to research on different applications and software programs in screen-titling, dubbing, re-speaking and screen-titling for the Deaf and Hard of Hearing, audio description and to obtain a training at professional agencies as well as to present a final assistance of quality.